ผลของการจัดกิจกรรมการอ่านโดยใช้แนวคิดสมองเป็นฐานที่มีต่อความสามารถ ในการอ่านจับใจความของนักเรียนชั้นประถมศึกษาปีที่ 3 - พงศ์วัชร์, ภณิตา; คล้ายมงคล, ยุรวัฒน์ (An Online Journal of Education, 2018)
This “Half Experiment-Based Research” was to study the outcome of learning by using reading activity - regarding Brain-Based Learning. It dealt with primary 3 students’ reading comprehension capability and comparison of using reading activity and normal study. The sample used were two classrooms from primary 3 students who are studying in the second half of the academic year (2016), Assumption Samutprakarn School. The tools used consisted reading comprehension activity plan, regarding Brain-Based Learning. The reading activity was based on the “5-Step of Brain-Knowledge”, including 1) Readiness, 2) Readers’ World Surfing, 3) Reading Cooperation, 4) Comprehension and 5) Creativity. The reading comprehension exercises showed that the reliability was 0.8. Analyzed by using average, percentage and standard deviation, it indicated that; the students trained with Brain-Based Learning had .05 % higher capability of reading comprehension